Effect of polypropylene fibers on the shear strength–dilation behavior of compacted lateritic soils - Silveira, Maitê Rocha [UNESP]; Rocha, Sabrina Andrade; Correia, Natália de Souza; Rodrigues, Roger Augusto [UNESP]; Giacheti, Heraldo Luiz [UNESP]; Lodi, Paulo César [UNESP] (MDPI, 2021)
The stress–dilatancy relationship for fiber-reinforced soils has been the focus of recent studies. This relationship can be used as a foundation for the development of constitutive models for fiber-reinforced soils. The present study aims to investigate the effect of recycled polypropylene fibers on the shear strength–dilation behavior of two lateritic soils using the stress–dilatancy relationship for direct shear tests. Results show that fibers improved the shear strength behavior of the composites, observed by increases in the friction angle. Fibers’ orientation at the sheared interface could be observed. The volumetric change during shearing was altered by the presence of fibers in both soils. Overall, results indicate that the stress–dilatancy relationship is affected by inclusions in the soil mix. Results can be used to implement constitutive modeling for fiber-reinforced soils.
Keywords: Drained test; Lateritic soil; Polypropylene fibers; Shear strength; Stress–dilatancy